Single chamber Solid Oxide Fuel Cells selective electrodes: A real chance with brownmillerite-based nanocomposites. (19th April 2021) - Bedon, Andrea; Viricelle, Jean Paul; Rieu, Mathilde; Mascotto, Simone; Glisenti, Antonella
Abstract: In this contribution brownmillerite-based nanocomposite cathode for Single-Chamber Solid Oxide Fuel Cells is developed. These cells can be very attractive especially for small and cheap devices because of the absence of seals. The efficiency of SC-SOFCs is strictly connected to the selectivity of anode and cathode, the bottleneck for this technology. The development of a cathode inert in fuel oxidation is particularly challenging. Our strategy is to start from a catalytically un-active support (CFA = Ca2 FeAl0.95 Mg0.05 O5 ) and induce the formation of iron oxide based nanoparticles, expected to activate oxygen. Symmetric (CFA + FeOx /CGO/CFA + FeOx ) and complete cells (CFA + FeOx /CGO/Ni-CGO) are studied in air and methane/oxygen 2:1 mixture. The Area Specific Resistance of CFA + FeOx is less than 1/3 that of CFA. The high selectivity allows to reach an efficiency of 25%; power still needs to be increased but we demonstrated the possibility to develop selective low cost electrodes. The effect of air, methane/oxygen exposure and the heat treatments were carefully investigated. Highlights: Selective cathodes for Single Chamber Solid Oxide Fuel Cells successfully obtained. Nanocomposites: iron based nanoparticles dispersed on Ca2 FeAl0.95 Mg0.05 O5 (FeOx + CFA). Symmetric FeOx + CFA/CGO/FeOx + CFA and complete FeOx + CFA/CGO/Ni-CGO cells. Cells are tested in air & CH4 /O2 mixture (1:2) converting 25% of the consumed fuel. Very cheap and environmentally sustainable devices for renewable diffused energy.